On mentoring, entrepreneurship and embracing technology - An interview with Tan Sri Dato’ Engr. Dr Francis Yeoh Sock Ping - Ooi, Suvarna (The Institution of Engineers, Malaysia, 2013)
Link to publisher’s homepage at http://www.myiem.org.my/